2022
DOI: 10.1002/cche.10583
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wheat flour with different farinograph and pasting characteristics on the surface tackiness of frozen cooked noodles

Abstract: Background and Objectives The sticky surface of cooked noodles seriously reduces consumer acceptance. This study investigates the effects of 12 wheat flour samples with different farinograph and pasting characteristics on the texture, sensory properties, and surface tackiness of recooked frozen cooked noodles (FCNs). Findings The recooked FCNs made of flour sample 1# with long dough stability time (DST) and high farinograph quality number (FQN) had a low surface tackiness (411 g) and high evaluation score (87)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…Farinograph characteristics can reflect the quality and processing property of wheat flour (Zhang et al, 2022). As shown in Table 1, compared with the control, wheat flour with added glutenin had lower DOS (86.67 FU) and FQN (67.33), and wheat flour with added gliadin had a higher DOS (151.00 FU) and lower FQN (58.67) ( p < .05).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Farinograph characteristics can reflect the quality and processing property of wheat flour (Zhang et al, 2022). As shown in Table 1, compared with the control, wheat flour with added glutenin had lower DOS (86.67 FU) and FQN (67.33), and wheat flour with added gliadin had a higher DOS (151.00 FU) and lower FQN (58.67) ( p < .05).…”
Section: Resultsmentioning
confidence: 99%
“…It suggested that the addition of glutenin or gliadin alone could not improve the quality of wheat flour as well as the addition of gluten. Besides, the previous study reported that the FCNs made of wheat flour with long DST and high FQN had low surface tackiness (Zhang et al, 2022). It is speculated that glutenin and gliadin addition alone may not decrease the surface tackiness of FCNs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations